Positive Solutions for p-Laplacian Fourth-Order Differential System with Integral Boundary Conditions - Jiqiang Jiang; Lishan Liu; Yonghong Wu (Discrete Dynamics in Nature and Society)
This paper investigates the existence of positive solutions for a class of singular p-Laplacian fourth-order differential equations with integral boundary conditions. By using the fixed point theory in cones, explicit range for λ and μ is derived such that for any λ and μ lie in their respective interval, the existence of at least one positive solution to the boundary value system is guaranteed.